2009
DOI: 10.1002/ange.200900423
|View full text |Cite
|
Sign up to set email alerts
|

A p‐Type NiO‐Based Dye‐Sensitized Solar Cell with an Open‐Circuit Voltage of 0.35 V

Abstract: In 2000, He et al. reported that the combination of a NiObased photoactive cathode with a TiO 2 -based photoanode produced a tandem device with an open-circuit voltage (V OC ) of 0.73 V, [1] which is the sum of the open-circuit potentials of the separate devices, where the TiO 2 -based electrode contributed 0.65 V and the NiO-based electrode 0.08 V. Tandem dye-sensitized solar cells (TDSCs), such as Hes, have suffered from the lack of research directed at the optimization of the photocathode, despite the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 24 publications
1
39
0
Order By: Relevance
“…Charge recombination between the photoreduced dye and the holes in the NiO is known to limit the APCE in p-type DSCs. 5,19,20,25 We have carried out visible and near-IR TA and TRIR experiments to determine the excited-state lifetimes of the dyes in solution and charge-separated state lifetimes of the dyes adsorbed on NiO. These experiments can help to determine Figure 7 shows the transient absorption spectra for the CAD 1 and CAD 2 excited states in dichloromethane solution 5 ps after excitation at 532 nm.…”
Section: ■ Resultsmentioning
confidence: 98%
“…Charge recombination between the photoreduced dye and the holes in the NiO is known to limit the APCE in p-type DSCs. 5,19,20,25 We have carried out visible and near-IR TA and TRIR experiments to determine the excited-state lifetimes of the dyes in solution and charge-separated state lifetimes of the dyes adsorbed on NiO. These experiments can help to determine Figure 7 shows the transient absorption spectra for the CAD 1 and CAD 2 excited states in dichloromethane solution 5 ps after excitation at 532 nm.…”
Section: ■ Resultsmentioning
confidence: 98%
“…This is consistent with the already reported valence band bending of NiO in the presence of a high concentration of a small cationic species such as lithium cation which was added in the electrolyte of p-type DSC in order to enhance their open circuit voltage. 80,81 …”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…A redox mediator such as triiodide or a cobalt 25,26 or iron 27 complex regenerates the dye and delivers electrons to the counter electrode in order to complete the photovoltaic circuit. 22,28,29 Recently, we found that simple diketopyrrolopyrrole based dyes (DPPBr and DPPCN2) and a "D-A" dyad (DPP-NDI are promising sensitizers for p-DSSCs and they can be used with both iodide and cobalt electrolytes (Chart 1). 13,14 Therefore, in order to achieve highly efficient systems, the charge recombination dynamic processes are the most critical factors to improve, in particular the competition between dye regeneration and recombination of the reduced dye with the hole in NiO.…”
Section: Introductionmentioning
confidence: 99%